2022
DOI: 10.1039/d2fo01028c
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3attenuates cisplatin-induced intestinal injury by inhibiting ferroptosis, oxidative stress, and ROS-mediated excessive mitochondrial fission

Abstract: Intestinal injury is one of the main side-effects of cisplatin (CP) chemotherapy, severely limiting the clinical application of cisplatin. Vitamin D3 is an essential nutrient for mammals and exists in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
3
6
0
Order By: Relevance
“…Previously, VD/VDR has been demonstrated to avert ferroptosis in hippocampal neuron via activating the Nrf2/HO-1 signaling [29] . Additionally, VD has been shown to inhibit ferroptosis in liver, kidney, intestine, and hypoxic-ischemic brain tissues through various pathways [30][31][32][33] , which is consistent with our observations. We found in vivo that vitamin D alleviates myocardial injury, likely by downregulating NRG1 expression and inhibiting Erbb4 activation.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, VD/VDR has been demonstrated to avert ferroptosis in hippocampal neuron via activating the Nrf2/HO-1 signaling [29] . Additionally, VD has been shown to inhibit ferroptosis in liver, kidney, intestine, and hypoxic-ischemic brain tissues through various pathways [30][31][32][33] , which is consistent with our observations. We found in vivo that vitamin D alleviates myocardial injury, likely by downregulating NRG1 expression and inhibiting Erbb4 activation.…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al showed that vitamin D alleviated cisplatin-induced intestinal injury in a 7-week-old male mice by inhibiting chemotherapy-induced ferroptosis, a recently discovered mechanism of cisplatin antineoplastic activity. It is likely that cisplatin also induces intestinal damage by this alternative form of programmed cell death, involving failure of the glutathione-dependent antioxidant defences, which results in unchecked lipid peroxidation and cell death [48]. Similar to previous studies, this study showed that vitamin D could reduce proinflammatory cytokines and regulate tight junction protein expression, preventing intestinal injury [48].…”
Section: Tight Junction Barrier Regulationsupporting
confidence: 85%
“…It is likely that cisplatin also induces intestinal damage by this alternative form of programmed cell death, involving failure of the glutathione-dependent antioxidant defences, which results in unchecked lipid peroxidation and cell death [48]. Similar to previous studies, this study showed that vitamin D could reduce proinflammatory cytokines and regulate tight junction protein expression, preventing intestinal injury [48].…”
Section: Tight Junction Barrier Regulationsupporting
confidence: 85%
“…However, when used at their nonlethal concentrations, all these lipids potently inhibited cell death triggered by the ferroptosis inducers, including IKE and RSL3 (Figure , Table S2). While the antiferroptotic properties of 7-DHC, vitamin D 3 , and the precursor of vitamin A, β-carotene, were previously demonstrated, to our knowledge, this is the first study that reports the inhibition of ferroptosis by the two forms of vitamin A including retinol and retinal. Previously, vitamin A was reported to function as either a pro-oxidant or an antioxidant, depending on oxygen tension in the tissues or organs. Here, vitamin A appeared to function as an antioxidant and a ferroptosis inhibitor.…”
Section: Discussionmentioning
confidence: 71%